Ethnische Säuberungen in der Moderne. Globale Wechselwirkungen nationalistischer und rassistischer Gewaltpolitik im 19. und 20. Jahrhundert - Schwartz, Michael 1963- (Quellen und Darstellungen zur Zeitgeschichte, 2013)
Ethnic "cleansing" is the dark side of modern democratization and the formation of nation states. Beginning in the 19th century, the Balkans and colonies outside Europe became the laboratories for this form of national problem solving. After 1914 these instruments of violence struck back on the European continent. Michael Schwartz describes the global context of ethnic "cleansing"